Large time increment approach for fatigue damage computations. Issue 1 (15th March 2018) - Alameddin, Shadi; Bhattacharyya, Mainak; Fau, Amelie; Nackenhorst, Udo; Néron, David; Ladevèze, Pierre
Abstract: This contribution focuses on the use of a new method to reduce the computational demands of fatigue damage computations using continuum damage mechanics. The LArge Time INcrement (LATIN) method incorporates a model order reduction approach namely the proper generalised decomposition (PGD). LATIN has been extended to tackle damage problems. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)